Khejri seed extract (KSE) enhances the growth, digestive, metabolic, and immunological responses of Labeo rohita fingerlings - Yadav, Rohitash; Jayant, Manish; Chadha, Narinder Kumar; Saini, Ved Prakash; Sawant, Paramita Banerjee; Ojha, Manohar Lal; Sharma, Bhanu Kumar; Meena, Dharmendra Kumar (Frontiers in Water, 2025)
The onset of diseases, combined with the reliance on therapeutics such as chemicals and antibiotics, as well as the alarming rise of antibiotic-resistant pathogen strains, postulates the urgent exploration of alternatives to antibiotics in semi-intensive and intensive aquaculture systems. In response to this critical need, a sixty-day feeding trial was conducted to evaluate the dietary effect of khejri seed extract (KSE) on the growth performance and immunological responses of rohu (Labeo rohita) fingerlings. Following this trial, a fifteen-day challenge study assessed the rohu fingerlings' resistance against Aeromonas hydrophilia. Four experimental diets were supplemented with different levels of khejri seed extract (KSE) viz. 0.0, 2.5, 5.0, and 7.5 g KSE kg−1 of diet and designated as C, KSE0.25, KSE0.50, and KSE0.75, respectively. The supplementation of dietary KSE led to significant improvements in growth performance and protein utilization in rohu fingerlings (P < 0.05). The activity of digestive (except amylase) and metabolic enzymes (except lactate dehydrogenase in muscle) activities varied significantly (P < 0.05). For the enzymes superoxide dismutase (SOD) and catalase (CAT), the observed trend was control > KSE0.25 > KSE0.50 > KSE0.75 in both pre- and post-challenge studies. Total serum protein showed significant variations (P < 0.05) in both pre- and post-challenge studies, with albumin and globulin concentrations being significantly higher in the KSE0.50 group compared to control during the post-challenge phase. Moreover, KSE supplementation significantly enhanced the respiratory burst activity and haematological parameters (except total leukocyte count in the pre-challenge and serum glucose levels in pre- and post-challenge study) of rohu fingerlings (P < 0.05). Following A. hydrophilia challenge, fish mortality significantly decreased with higher dietary KSE levels (P < 0.05), reaching the lowest mortality in the KSE0.50 group. These results suggest that supplementing the diet with 5.0 g kg−1 khejri seed extract can effectively enhance growth, improve feed conversion, boost immunity, and increase survival against A. hydrophila infection in rohu fingerlings.